Communicating About Water in the Floridan Aquifer Region: Part 3— How the Right Messages and Messengers Can Increase Bipartisan Support for Water Policy - Sadie Hundemer; Shenara Ramadan (EDIS)
When water policies are introduced, they may not be universally supported. One stakeholder group or political party may be “for” the policy and contend that the public should vote “yes.” They may argue that the policy is fair to the parties involved or that it shows loyalty to affected communities. These are moral arguments used to sway public support. An opposing stakeholder group or political party may also issue moral arguments “against” the policy. They may argue that the public should vote “no” because the policy is not fair or is disloyal to impacted communities. In competitive policy scenarios like these, at least two factors affect public support for the policy – moral arguments and the identities of the communicators. Understanding how each of these factors influences policy preferences is key to creating a communication that is conducive to broad public support.